Reverse Bayesianism: A clarification and generalization - Edi Karni; Quitze Valenzuela-Stookey; Marie-Louise Vierø (Queen's University, Department of Economics, 2018)
In this note we clarify and generalize the main result in Karni and Viero (2013) by allowing the discovery of new consequences to nulllify some states that were non-null before the discovery.
Keywords: D8; D81; D83; 330; Growing awareness; reverse Bayesianism; falsification